Low contact-resistivity and high-uniformity Ni/Au ohmic contacts on Si nanomembranes grafted to Si substrates via low-temperature rapid thermal annealing. (15th November 2022) - Kim, Jisoo; Gong, Jiarui; Lin, Wei; Lal, Shalini; Su, Xin; Vincent, Daniel; Cho, Sang June; Zhou, Jie; Min, Seunghwan; Kim, Donghyeok; Ma, Zhenqiang
Abstract: Grafted lattice-mismatched semiconductor heterostructures have the potential to simultaneously achieve low on-resistance and high breakdown performance. These novel semiconductor devices are typically fabricated by grafting single-crystal semiconductor nanomembrane (NM) layers onto a foreign substrate. The optimal temperature for grafting often prevents the use of high temperatures to achieve optimal ohmic contacts. Herein, we present a method to form low temperature Ni/Au ohmic contacts for the anode electrode to a p + Si NM that is grafted to a Si substrate. Ohmic contact resistivity ( ρ c ) and its device-to-device uniformity are characterized against different annealing temperatures and are also compared against contact resistivity of p + SOI structure. Low resistivity ohmic contacts ( ρ c = 5.92 × 10 -6 Ω cm 2 ) and high uniformity were achieved on grafted NM structure. Demonstration of low ρ c for NM-transferred layers via a low-temperature metallization scheme achieves an important step towards further developing high performance lattice-mismatched heterostructure-based devices.